Seismic performance of RC frame-shear wall structures with vertical setback. (October 2021) - Jiang, Huanjun; Huang, Youlu; He, Liusheng; Huang, Tian; Zhang, Shaojing
Abstract: The reinforced concrete (RC) frame-shear wall structure is a typical structural system for modern high-rise buildings. This paper investigates the influence of vertical setback on its seismic performance through elasto-plastic time history analysis on three groups of models under different levels of earthquakes excitation. The studied variables include setback percentage, local lateral stiffness ratio and setback position, which cause vertical irregularity to the structure. It is confirmed that existence of setback increases the inter-storey drift ratio at the setback position due to the sudden change of lateral stiffness thereby. Compared to the structure without setback but having the similar local lateral stiffness, the maximum inter-storey drift ratio is smaller due to the reduced mass associated with the existence of setback. To quantify vertical irregularity, limitation on the local lateral stiffness ratio can be relaxed to some extent for structures with setback. Considering the resulted variation of inter-storey drift ratio, setback percentage and lateral stiffness ratio are equally important. Along the height, setback at the middle height gives larger inter-storey drift ratio and seismic force.